Ambush - Nickless, Barbara (Sydney Rose Parnell series, 2019)
The gripping third book in the bestselling Sydney Rose Parnell series. Railway cop and former Marine Sydney Parnell is on the hunt. So is a killer she knows only as the Alpha. They're in a race to find Malik, an eleven-year-old Iraqi boy with secrets to guard. Sydney wants to help him. The Alpha wants him dead. From the dark alleys of Mexico City to the mean streets of Denver, Sydney and her K9 partner, Clyde, use their wits and determination to chase down the ruthless killer. But when their path collides with his, Sydney realizes just how far-reaching and sinister the Alpha's past is. And how far he's willing to go to save his secrets.